Basic vital cardiac support. Training to relatives of patients with acute miocardial infarction - Brandy Viera Valdés; Paula Aguila Solis; Francisco Valladares Carvajal; Marcos D. Iraola Ferrer; Pablo. A. Rodríguez (Medisur)
Background: Title: Basic vital cardiac support. Training to relatives of patients with acute miocardial infarction. The cardiorespiratory reanimation is a proved procedure that can save a human life in case of a cardiorespiratory stop. For three years it is imparted in the University Hospital of Cienfuegos, a training for this procedure, to the family of patients with sharp myocardic infarction. Objective: To evaluate the knowledge acquired by the relatives of the patients during the training. Methods: A prospective-descriptive study was carried out in the period between January 2002 and December 2004; the sample engulfed all those trained during this period (752 relatives). Results: Only the 4 % of relatives had some previous knowledge on the topic; most of them were able to acquire the practical and theoretical abilities proposed in the objectives of the course. Conclusions: The putting in practice of this course is a preventive strategies, whose results can only be evaluated at long or median term; through future studies that corroborate their efficiency, according to the out-hospital mortality behaviour for acute miocardial infarction.